2012
DOI: 10.1186/1754-6834-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Tracking dynamics of plant biomass composting by changes in substrate structure, microbial community, and enzyme activity

Abstract: BackgroundUnderstanding the dynamics of the microbial communities that, along with their secreted enzymes, are involved in the natural process of biomass composting may hold the key to breaking the major bottleneck in biomass-to-biofuels conversion technology, which is the still-costly deconstruction of polymeric biomass carbohydrates to fermentable sugars.However, the complexity of both the structure of plant biomass and its counterpart microbial degradation communities makes it difficult to investigate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Cellulolytic and ligninolytic microbiota were much less represented. Their counts were found several orders of magnitude below those of other functional groups (counts ranged 10 5 -10 6 cfu g À1 ) and they were mainly detected at final composting stages as it has been previously reported (Wei et al, 2012). In general, microbial evolution profiles were quite similar in both control and inoculated piles, however, significant differences for all microbial groups were found and counts were always higher in the inoculated piles, especially after the first inoculation had been performed (IMES).…”
Section: Evolution Of Functionality Of Microbial Communitiesmentioning
confidence: 53%
“…Cellulolytic and ligninolytic microbiota were much less represented. Their counts were found several orders of magnitude below those of other functional groups (counts ranged 10 5 -10 6 cfu g À1 ) and they were mainly detected at final composting stages as it has been previously reported (Wei et al, 2012). In general, microbial evolution profiles were quite similar in both control and inoculated piles, however, significant differences for all microbial groups were found and counts were always higher in the inoculated piles, especially after the first inoculation had been performed (IMES).…”
Section: Evolution Of Functionality Of Microbial Communitiesmentioning
confidence: 53%
“…It has been suggested that multiple CBMs may counteract the loss of binding affinity between thermophilic enzymes and their substrates at elevated temperatures [30]. During a typical composting process, compost microbiota experience a thermophilic phase (above 50 °C) for about one week and much longer mesophilic phases (20–50 °C) [6, 31]. It remains to be seen whPaenibacillusether compost-derived microbial consortia employ a similar strategy to enable strong binding to insoluble polysaccharide substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Although fungi are present throughout the composting process, recent studies suggest that thermophilic fungi are much less abundant than bacteria and that fungal biomass degradation activity is limited during the thermophilic phase [32,33]. The present study therefore focused on the prokaryotic population and the DNA extraction protocol used aimed at isolating prokaryotic DNA.…”
Section: Discussionmentioning
confidence: 99%